The Influence of School Environment on Students' Mental and Post-Traumatic Growth: A Quantitative Study - Marzhuhriya Khoirunnisa; Sadam Fajar Shodiq (STAI Hubbulwathan Duri, 2025)
Mental health among adolescents is a critical concern with profound implications for individuals, families, and educational systems. In school settings, the environment can serve as a protective factor that fosters mental well-being and supports post-traumatic growth (PTG), particularly among students exposed to stress or adversity. This study aimed to explore the associative relationship between the school environment, students' mental health, and post-traumatic growth. Employing a descriptive quantitative design, the study involved 210 students from grades XI and XII at MA Taruna Al-Qur’an, selected using simple random sampling. Data were collected through a Likert-scale questionnaire covering perceptions of school environment, mental health, and PTG. Structural Equation Modeling (SEM) was applied using SmartPLS 4.0 to assess the strength of associations without implying causality. The analysis revealed that the school environment accounted for 86.8% of the variance in students' mental health and 89% in post-traumatic growth. Both associations were found to be statistically significant, with strong reliability and validity scores across all measurement constructs. These findings highlight the strategic role of a supportive school environment in promoting adolescents’ psychological resilience and recovery. Creating a safe, inclusive, and empathetic school climate can significantly enhance students’ capacity to maintain mental well-being and experience positive growth following adversity. Educational institutions are encouraged to integrate social-emotional learning and trauma-informed practices into their environments to further support student development.